Implementation Open Bidding For Middle Managers (JPT Pratama) Position In The National Archives Of The Republic Of Indonesia (ANRI) - Mita Restu Permatasari; Eko Prasojo (Cakrawala Repositori IMWI, 2023)
Indonesia is one of the countries that has carried out personnel reform by implementing open recruitment and selection for Primary High Leadership Positions (JPT) which are currently being carried out openly using a merit system. The National Archives of the Republic of Indonesia as a non-ministerial government institution has also implemented this policy in conducting open recruitment and selection by implementing a merit system. The purpose of this study is to analyze how the implementation of and problems with policy implementation in filling recruitment and open selection for Primary High Leadership Positions (JPT) in personnel management in Indonesia, especially in the National Archives of the Republic of Indonesia. The research method in this paper is qualitative using a post-positivism approach. Data obtained through observation obtained from journals, documentation and interviews were analyzed descriptively in a relevant and accurate manner. The results of the study show that the implementation of the implementation of open selection at the Pratama High Leadership Position (JPT) has not fully gone well so it is necessary to take steps to be able to make strategic improvements in an effort to implement effective bureaucratic reform so that the practice of KKN (Corruption, Collusion and Nepotism) can be avoided. Thus, it is necessary to improve the practice of civil service reform in Indonesia, especially in the implementation of open selection so that it can provide public services in a selective, objective and better supervisory manner based on applicable policies and regulations.